Non-native Species Surrounding Protected Areas Influence the Community of Non-native Species Within Them - Holenstein, Kathrin; Simonson, William D.; Smith, Kevin G.; Blackburn, Tim M.; Charpentier, Anne (Frontiers in Ecology and Evolution, 2021)
Protected areas (PAs) are a key element of global conservation strategies aiming to protect habitats and species from various threats such as non-natives species (NNS) with negative ecological impacts. Yet little is known about the mechanisms by which PAs are colonized by NNS, and more specifically the role of colonizing events from surrounding areas. Here, we compared terrestrial and freshwater non-native plants and animals recorded in Norwegian PAs and in 5-km belts around them, using the database of the Norwegian Biodiversity Information Centre Species Map Service. Our analysis included 1,602 NNS and 671 PAs. We found that NNS were recorded in only 23% of the PAs, despite the fact that 90% of the 5-km belts were colonized by at least one NNS. A Zero-inflated negative binomial regression model showed that the number of NNS in the 5-km belts was a strong explanatory variable of the NNS richness inside PAs. Other significant variables included the surface area of the PA, mean human population density in the PA, main type of habitat and accessibility of PAs. We also observed similarity in the species in and around the PAs, with, on average, two thirds of the NNS present in a specific PA also present in its 5-km belt. Furthermore, NNS were recorded in PAs on average 4.5 years after being recorded in the 0–5 km belts, suggesting a dynamic of rapid colonization from the belts to the PAs. Invasive NNS represented 12% of NNS in the belts but 40% in the PAs. This difference was related to the higher abundance of invasive NNS in the belts. Our results highlight the necessity of expanding the focus of NNS management in PAs beyond their boundaries, in particular to prevent incursions of NNS with high negative ecological impact.